Etnometodologi Sebagai Pendekatan Baru dalam Kajian Ilmu Komunikasi - Susilo, Daniel (Jurnal Studi Komunikasi, 2017)
This article would to challenging with literature about new approach to solve the communications science issue. Ethnometodology as an emerging approach in the era of the modern Sociology has not been sufficiently widely adopted by Communications Academician in Indonesia. Inversely proportional to the phenomenology that has enjoyed widespread acceptance among academics Indonesia. In this literature study tried to explore the possibilities of a communication problems can be solved by ethnometodology as research method. The conclusion of this article is the possibility of adoption of Ethnometodologi as a new variety in Communication Research Methods at Indonesia. Keywords: Ethnomethodology, Research on communication, new methods